Assessing the risk of antimicrobial resistance and potential environmental harm through national-scale surveillance of antimicrobials in hospital and community wastewater - Byrnes, Neil Andrew; Silvester, Reshma; Cross, Gareth; Weightman, Andrew J.; Jones, Davey L.; Kasprzyk-Hordern, Barbara (Environment international, 2025)
[Display omitted] •Ciprofloxacin and clarithromycin concentrations frequently above PNECs.•High concentrations of sulfamethoxazole and trimethoprim found in hospital effluent.•Hospital effluent wastewater is a hot spot for induction of antimicrobial resistance.•Direct disposal of antimicrobials was identified in hospital effluent wastewater.•Treatment of hospital effluent at source recommended to mitigate risks. Antimicrobial resistance (AMR) is a major public health concern. Antimicrobial residues enter wastewater where their continued presence can lead to an increased risk of AMR while also causing environmental harm when untreated wastewater is discharged into the environment. This research presents the antimicrobial residue surveillance results of a national-scale wastewater sampling campaign across Wales. Wastewater from 15 sites—effluent from 7 hospitals and influent from 8 community wastewater treatment plants—was collected for 5 consecutive days monthly from May–July 2023. This campaign captured more than 30 % of the Welsh population and over 30 % of the population receiving care as hospital inpatients. Using a quantitative approach, over 175 unique wastewater samples were analyzed by ultra-performance liquid chromatography tandem mass spectrometry (UPLC–MS/MS) for more than 40 antimicrobials including: β-lactams, macrolides, quinolones, sulfonamides, a veterinary antibiotic, an antifungal, antivirals, and numerous metabolites. The most prevalent antimicrobials were clarithromycin, its metabolite N-desmethyl clarithromycin, fluconazole, and trimethoprim as they were detected in all samples. Sulfamethoxazole concentrations ranged from 724–28031 ng/L and trimethoprim ranged from 785–44539 ng/L in hospital effluent—concentrations significantly higher than those reported in published literature. In hospital wastewater, many antimicrobials were present at concentrations which were orders of magnitude higher than their respective predicted no-effect concentrations (PNECs) for antibiotic resistance selection (e.g., metronidazole, trimethoprim). These concentrations create a selective pressure which can drive AMR emergence. Furthermore, some antimicrobials remained at high-risk concentrations even after dilution in community wastewater (e.g., ciprofloxacin, clarithromycin). Environmental risk assessments also identified clarithromycin and ciprofloxacin as agents of concern while vancomycin posed the highest environmental risk (concentrations ca. 1000–38000-fold > PNEC in hospital effluent) should this wastewater enter the environment untreated (e.g., combined sewer overflows). Instances of direct disposal of antimicrobials were clearly identified in hospital wastewater. These results demonstrate the importance of regular monitoring of AMR and potential environmental risk posed by antimicrobials in wastewater, while demonstrating the need for comprehensive national action (e.g., treatment of hospital wastewater on-site, tertiary/quaternary treatment of community wastewater, tailored stewardship programs, focussed control efforts on high-risk antimicrobials) to minimize risks to public health and the environment.